2009
DOI: 10.1002/bit.22283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human patient plasma ex vivo treatment on gene expression and progenitor cell activation of primary human liver cells in multi‐compartment 3D perfusion bioreactors for extra‐corporeal liver support

Abstract: Cultivation of primary human liver cells in innovative 3D perfusion multi-compartment capillary membrane bioreactors using decentralized mass exchange and integral oxygenation provides in vitro conditions close to the physiologic environment in vivo. While a few scale-up bioreactors were used clinically, inoculated liver progenitors in these bioreactors were not investigated. Therefore, we characterized regenerative processes and expression patterns of auto- and paracrine mediators involved in liver regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…1C). A detailed description of the bioreactor structure is given elsewhere (Schmelzer et al, 2009). In this study, a downscaled bioreactor with a cell compartment volume of 2 ml was used (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C). A detailed description of the bioreactor structure is given elsewhere (Schmelzer et al, 2009). In this study, a downscaled bioreactor with a cell compartment volume of 2 ml was used (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that porcine or human liver cells retain in vivo-like properties and are arranged in tissue-like structures including formation of biliary canalicular networks and neo-sinusoids when cultured in a perfused 3D bioreactor (Zeilinger et al, 2004;Schmelzer et al, 2009). More importantly, liver-specific functions such as urea and albumin synthesis, glucose metabolism, and P450 activities were all maintained for at least 14 days in this type of bioreactor (Zeilinger et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To mimic the situation in the liver, fresh human hepatocytes can be cultured in bioreactors, which enables a 3D structure, cell-cell contact, and a constant medium flow and oxygen supply that are important for the intracellular functions and maintenance of the cell polarity (Tilles et al, 2001;Zeilinger et al, 2004;Schmelzer et al, 2009;Vinci et al, 2011). It has been shown previously that fresh human hepatocytes can maintain their liver-specific functions such as urea and albumin synthesis, glucose metabolism, and P450 activities for at least 14 days in 3D cultures (Zeilinger et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…As well as being used clinically [21], they are being utilised as in vitro models, like the scaling down of a 3D perfusion multicompartment hollow fibre liver bioreactor for use in in vitro pharmacological studies [22]. This bioreactor consists of three interwoven sets of hollow fibre, two for counter current medium perfusion and one for gas supply (Fig 1).…”
Section: Status Of Bioreactors In the Development Of In Vitro Modelsmentioning
confidence: 99%